Knowledge on Urinary Incontinence among Women in a Community at Barahachhetra, Nepal - Basnet, Urmila; Yangden, Namita; Mandal, Punam Kumari (Journal of Research and Development, 2023)
Urinary Incontinence is a condition in which involuntary loss of urine is a social or hygienic problem for the patient. Urinary incontinence is regarded as a disgraceful situation, with a negative effect on the quality of life, and is usually kept disguised. It is an important problem leading to physical, social, psychological, sexual, and economic problems among women of all age groups. The aim of this study was to assess knowledge of urinary incontinence among women in a community at Barahachhetra. A descriptive study was conducted among women aged 40-65 years residing in Barahachhetra-5. A non-probability purposive sampling technique was used to gather data from 105 women using a semi-structured interview schedule with Face-to-face interviews. SPSS version 16 (SPSS Inc., Chicago, III., USA) was used for data entry and analysis. Descriptive analysis and inferential statistics i.e., chi-square test was used to find the association of the level of knowledge with selected demographic variables. This study revealed that out of 105 respondents, 21% had good knowledge and 59% had average knowledge on urinary incontinence which concluded that only less than one-fourth of respondents have good knowledge and the level of knowledge is not associated with selected demographic variables. It is recommended that awareness programs on urinary incontinence should be conducted at the community level by concerned authorities.